Coconut oil and medium-chain fatty acids attenuate high-fat diet-induced obesity in mice through increased thermogenesis by activating brown adipose tissue - Gao, Yunxiao; Liu, Yiwen; Han, Xue; Zhou, Fang; Guo, Jielong; Huang, Weidong; Zhan, Jicheng; You, Yilin (Frontiers in Nutrition, 2022)
Coconut oil (CO) and its main ingredients, medium-chain fatty acids (MCFA), present many benefits. Whether MCFA and CO play an equally valuable role in anti-obesity remains unclear. This study compared the anti-obesity effects of CO and MCFA (octanoic acid (C8:0) and decanoic acid (C10:0)) to gain insight into the underlying mechanism. Male C57BL/6J mice were fed either a low-fat diet (LFD) or high-fat diet (100% HFD) replaced with 2.5% MCFA (97.5% HFD + 2.5% MCFA) or 5% CO (95% HFD + 5% CO) for 17 weeks. CO and MCFA ameliorated the HFD-induced abnormal body and adipose depot weights, insulin sensitivity, and energy expenditure, which was associated with brown adipose tissue (BAT) thermogenesis. Furthermore, CO enhanced the expression of thermogenesis markers in BAT, which was consistent with increased BAT activity. CO showed a better effect than MCFA in activating BAT to increase thermogenesis and energy metabolism to combat obesity, which may be attributed to the cooperation of MCFA and other substances in CO. This work provides evidence for the anti-obesity effects of CO, which could be a better alternative to lard in daily diet, rather than pure MCFA.